Parliament, citizen and environmental policies: the perception of participants in public hearings in the Brazilian Chamber of Deputies on the environment - de Barros, Antonio Teixeira (Desenvolvimento e Meio Ambiente, 2021)
The article analyzes the perceptions of citizens who participated in the public hearings promoted by the Environment and Sustainable Development Commission (CMADS) of the Chamber of Deputies during 2019. A total of 552 questionnaires were applied, which corresponds to a sampling of 71, 22% of the audience. The hypothesis that guides the study is that participation in public hearings is motivated by a set of interrelated factors, such as the link with environmental entities, professional performance in the environmental area, and identification with ecologically oriented parties. The data confirm this hypothesis and show that there is a relatively assiduous audience at the hearings because of these factors. The perceptions present criticisms to the performance of parliamentarians and representatives of government agencies in the debate and the low performance of the National Congress in the area of environmental policies. On the other hand, the participation of representatives of ecological entities is assessed by the respondents as positive, since it contributes to qualify the discussion.